Dinamika Penegakan Hukum Lingkungan di Kalimantan Tengah: Paradoks Ekonomi dan Konservasi Hutan - Raden Alya Nabila; Intan Nuraini (STIS DAFA MATARAM, 2026)
This study aims to analyze the dynamics of environmental law enforcement in Central Kalimantan, examine the policy paradox between economic interests and forest conservation, and identify the factors affecting the effectiveness of environmental law enforcement. This research employs a qualitative approach using a descriptive-analytical method through a literature review of legislation, official reports, and scientific publications. The findings indicate that environmental law enforcement remains fluctuating. In 2019, the burned forest and land area reached 202,486 hectares, while deforestation due to land conversion resulted in the loss of approximately 42,000 hectares of natural forest. The study also reveals that law enforcement has not been fully effective due to economic pressures, pro-investment policies, and structural factors, including overlapping regulations and inconsistent data, as well as disparities in law enforcement between small-scale offenders and large corporations. The contribution of this study lies in its integrative analysis that connects legal, economic, and structural aspects in explaining the dynamics of environmental law enforcement in Central Kalimantan, thereby providing a basis for strengthening forest protection policies and improving the effectiveness of environmental law enforcement.